Penurunan Hemoglobin Persisten Pascasectio Caesarea pada HELLP Syndrome: Laporan Kasus Tantangan Diagnostik dan Pendekatan Terapi Kortikosteroid: Unresolved Hemoglobin Decline After Cesarean Delivery in HELLP Syndrome: Diagnostic Challenges and the Role of Corticosteroid Therapy — A Case Report - Sukmara, Uta Provinsiana (Jurnal Sains dan Kesehatan, 2026)
Placental abruption associated with severe preeclampsia and HELLP syndrome is a critical obstetric condition that may rapidly progress to hematologic complications. We report a 29-year-old woman, gravida 2 para 1, at 21–22 weeks’ gestation, presenting with abdominal pain and vaginal bleeding, with chronic hypertension and obesity. Initial evaluation revealed severe hypertension, anemia, leukocytosis, mild thrombocytopenia, and ultrasonographic intrauterine fetal death, suggesting placental abruption with superimposed preeclampsia and suspected partial HELLP syndrome. Emergency cesarean section under spinal anesthesia confirmed placental abruption intraoperatively. Postoperatively, progressive hemoglobin decline unresponsive to initial transfusion occurred, accompanied by thrombocytopenia and elevated coagulation markers despite relative hemodynamic stability, creating a dilemma between recurrent bleeding and microangiopathic hemolytic anemia. Exploratory relaparotomy under general anesthesia showed no active bleeding source, only diffuse oozing, supporting HELLP syndrome with consumptive coagulopathy. The patient required ICU care with mechanical ventilation and aggressive blood component transfusion for severe anemia. Adjunctive corticosteroid therapy improved. Keywords:          HELLP syndrome; microangiopathic hemolytic anemia; obstetric anesthesiology; placental abruption   Abstrak Solusio plasenta yang disertai preeklampsia berat dan HELLP syndrome merupakan kondisi obstetri kritis yang dapat berkembang cepat menjadi gangguan hematologis dan multisistem yang mengancam nyawa. Dilaporkan seorang perempuan 29 tahun, gravida 2 para 1, usia kehamilan 21–22 minggu, datang keluhan nyeri perut dan perdarahan pervaginam, terdapat riwayat hipertensi kronik dan obesitas. Evaluasi awal menunjukkan hipertensi berat, anemia, leukositosis, trombositopenia ringan, serta ultrasonografi intrauterine fetal death adanya kecurigaan solusio plasenta dan superimposed preeklampsia dd/suspek partial HELLP syndrome. Pasien menjalani sectio caesarea emergensi dengan anestesi spinal, dan temuan intraoperatif solusio plasenta. Pascaoperasi terjadi penurunan hemoglobin progresif yang tidak responsif terhadap transfusi awal, disertai trombositopenia dan peningkatan marker koagulopati, meskipun hemodinamik relatif stabil, menimbulkan dilema antara perdarahan berulang dan anemia hemolitik mikroangiopatik. Re-laparotomi eksploratif tidak menemukan sumber perdarahan aktif, mendukung HELLP syndrome beserta koagulopati konsumtif. Pasien dirawat di ICU dengan ventilasi mekanik akibat anemia berat (Hb 4,7 g/dL). Transfusi komponen darah agresif disertai terapi kortikosteroid memberikan perbaikan klinis dan hematologis bermakna hingga pasien pulih dan dipulangkan. Kata Kunci:         anemia hemolitik; anestesiologi obstetric; HELLP syndrome; mikroangiopatik; solusio plasenta